Gestão de OEE em uma empresa do setor de saúde - Moraes, Eduarda Peinado [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The increasingly competitive and dynamic market demands flexibility and high efficiency from the companies. In order to maintain high standards, it is necessary to invest in continuous improvement and to manage the production processes efficiently. Therefore, companies have been looking for methods and tools to help and simplify this path. An indicator capable of presenting the performance of a process and, at the same time, the effects caused by an event in the total performance is the Overall Equipment Effectiveness (OEE). This work aims to study the OEE management in a multinational company in the healthcare segment, located in Vale do Paraíba. The methodology used is action research. The management system is described, as well as the process of identifying problems and submitting improvement actions. The methods applied made possible to detect the biggest interferences in the OEE results and, after the implementation of improvement actions, it presented satisfactory results

O mercado atual, cada vez mais dinâmico e competitivo, exige das empresas flexibilidade e elevada eficiência. Para manter um alto nível é preciso investir em melhoria contínua e deter uma gestão eficaz dos processos produtivos. Dessa forma, as empresas têm buscado métodos e ferramentas que auxiliem e simplifiquem esse caminho. Um indicador capaz de apontar a performance de um processo e que, ao mesmo tempo, permite entender o efeito que um evento gera no resultado final é a Eficácia Global do Equipamento (OEE). Este trabalho tem como objetivo estudar a gestão de OEE em uma empresa multinacional do setor de saúde, localizada no Vale do Paraíba. O método utilizado foi a pesquisa-ação. Buscou-se detalhar a forma de gestão, bem como o processo de identificação de problemas e proposição de ações de melhoria. Os métodos utilizados puderam detectar as maiores interferências nos resultados de OEE e, após as melhorias, apresentaram resultados satisfatórios
Management of OEE in a company of the health sector
Keywords: Gestão da qualidade total; Controle de qualidade; Controle de processo; Total quality management